Seed mix type but not planting method or seed priming affect grassland restoration outcomes: a greenhouse trial. Issue 2 (3rd April 2019) - Demmer, Stuart; Tedder, Michelle J; Kirkman, Kevin P
Abstract : Commercial seed mixes and various mechanical planting methods have been implemented to overcome barriers to successful restoration of degraded grasslands but their effectiveness in aiding the restoration process has been understudied. Harvested seed must be cleaned of chaff to allow mechanical planting, which can exclude small seeds. We propose that fluid seed drilling techniques (suspending uncleaned harvested seed in a cellulose-based gel matrix, which may then be injected into the soil with a mechanical planter) may overcome these challenges. As a preliminary investigation of the proposed method we designed a greenhouse pot trial experiment aimed at quantifying restoration success through the measurement of seedling recruitment, biomass production and composition responses of commercial and harvested seed mixes under simulated fluid seed drilling and smoke water priming (collectively termed application method). These data were analysed using generalised linear modelling and multivariate analyses. Commercial mixed seed resulted in greater recruitment, whereas harvested seed produced the greatest biomass production. There was large multivariate separation between seed types and seed type × application method centroids for recruitment responses and only seed type for biomass responses. Application method had minimal effects on restoration measurements whilst seed type greatly affected these measurements. Careful selection of the restoration seed mix is advised.